Newborn with a periocular rash. - Makhdoom, A.Z.; Franco-Fuenmayor, M. (European Journal of Pediatric Dermatology, 2023)
Neonatal lupus erythematosus (NLE) is caused by the transplacental transfer of maternal anti-Ro/La autoantibodies. NLE can result in multiple manifestations, most typically cardiac or cutaneous in nature. Cutaneous NLE will resolve spontaneously in the first year of life, whereas cardiac NLE has a high mortality rate (20%) and a significant proportion of patients affected will need a pacemaker (60%). Here was reported the case of a newborn with NLE, born to a mother affected by systemic lupus erythematosus.